2017
DOI: 10.1038/s41598-017-06768-x
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbial community structure and catabolic activity are significantly degenerated in successive rotations of Chinese fir plantations

Abstract: This study examined the hypotheses that soil microbial community composition and catabolic activity would significantly degenerated by consecutive monoculture in Chinese fir plantations. The phospholipid fatty acids (PLFA) and community level physiological profiles (CLPP) methods were used to assess the variations of soil microbial community among the first rotation Chinese fir plantation (FCP), the second rotation plantation (SCP) and the third rotation plantation (TCP). The total content of PLFA biomarkers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 39 publications
8
28
0
Order By: Relevance
“…The cloud model has better universality estimations, risk assessment [42], time series prediction and analysis [43], and comprehensive evaluation [44], but it has not yet been applied in soil fertility-related research. The evaluation results from the cloud model in this study are consistent with previous studies and consistent with the reality [6,45]. The cloud model used in this study provides a new method of studying soil characteristics.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The cloud model has better universality estimations, risk assessment [42], time series prediction and analysis [43], and comprehensive evaluation [44], but it has not yet been applied in soil fertility-related research. The evaluation results from the cloud model in this study are consistent with previous studies and consistent with the reality [6,45]. The cloud model used in this study provides a new method of studying soil characteristics.…”
Section: Discussionsupporting
confidence: 90%
“…The construction of Chinese fir plantations can not only improve the income of local farmers [3] but also improve the natural ecological environment [4,5]. Nevertheless, with the continuous expansion of planting area, soil degradation has taken place in some regions [6,7]. How to maintain soil fertility and strengthen the sustainable development of the forestry industry has become the focus of local governments and scholars.…”
Section: Introductionmentioning
confidence: 99%
“…Although there were no notable differences in the absolute abundances of PLFA biomarkers across the four stand ages, the ratios of PLFA biomarkers significantly differed among stands (Figure 3). Consistent with the study of Yang et al [52] and contrary to the result of Cavagnaro et al [54], we found that the F/B ratio significantly decreased in older stands, suggesting a lower soil nutritional stress with tree growth, as bacteria tend to accumulate when soil nutrients are enough while a shift towards fungal dominance will occur when soil nutrient contents decline [55,56]. In addition, the same as the findings of Liu et al [24], we also found decreased G+/G− ratio with increasing stand age, indicating accumulation of easily-decomposable substrates in soils [29,50].…”
Section: Effect Of Stand Age On Microbial Communities and Enzyme Actisupporting
confidence: 89%
“…The significant links between net nitrogen mineralization rate and microbial community structure are not surprising given that changes in soil microbial community have a close correlation with soil N cycling [58] and N mineralization in soil is a result of microbial activity [59]. However, inconsistent with Wu et al and Wan et al who both mentioned that soil C/N ratio was linked with soil biological indicators of Chinese fir forests [55,60], we did not observe obvious correlations between C/N ratio and biological variables. This result might be explained by the small range of C/N ratio (11.94-12.62) compared to other studies on Chinese fir [48].…”
Section: Relationships Between Physicochemical Properties and Microbimentioning
confidence: 96%
“…Replanting diseases are observed in many cultivated tree species, including Chinese fir, Pinus elliottii , Picea abies , and Eucalyptus spp. ( Wu et al, 2017 ). The depletion in soil nutrients ( Bennett et al, 2012 ), the autointoxication of root exudations ( Araya et al, 2012 ), and the imbalance of rhizospheric microflora ( Wu et al, 2016a ) are thought to be the main reasons for CMP.…”
Section: Introductionmentioning
confidence: 99%